Strategic Human Resource Management in the Face of Global Economic Turmoil: Navigating Challenges, Fostering Resilience, and Ensuring Sustainable Workforce Practices - N E, Dr. Pradeep; H K , Keerthi; Panda , Jigyansa (Electronic Journal of Business and Management, 2023)
The objective of this study is to examine the complex dynamics of worldwide economic instability and its consequences for Strategic Human Resource Management (SHRM). The study examines the interrelated elements that contribute to economic instability, such as pandemics, financial crises, and geopolitical tensions, by considering historical perspectives and present findings. This study analyzes fundamental theories and frameworks to guide human resources practices during periods of economic turmoil, with a particular focus on the significance of proactive methods for recuperation and adaptability. The research emphasizes the long-lasting influence of the COVID-19 issue, specifically in determining the patterns of remote labour and tactics for managing supply chains. Additionally, this study explores the strategic aspects of sustainability considerations and emphasizes the importance of crossindustry collaboration in promoting resilience, particularly within the context of small and medium companies (SMEs). Moreover, it tackles the changing HR methods for managing people, developing the workforce, and managing risks in response to dynamic economic environments. In general, this study highlights the crucial significance of Strategic Human Resource Management (SHRM) in efficiently addressing global economic difficulties. It emphasizes the need for ongoing research and improvement to successfully adapt to changing conditions.